Developing a new methodology to identify global hotspots of climatic risk and food security, including a meta-analysis of four decades of climate research in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The methodology has already been published as a journal article. The same method can be used to identify potential hotspots at sub-national scales for policy planning.